2011
DOI: 10.4236/jct.2011.23048
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Polymorphisms of Glutathione S-Transferase GSTT1 and GSTM1 With the Response to Chemotherapy In Mexican Women with Advanced Breast Cancer

Abstract: Introduction: Breast cancer is a common disease diagnosed in Mexican women and the first leading cause of death [1]. Heterogeneity in patients’ response to treatment is consistently observed across populations. Glutathione S-transferases (GSTs) are involved in the metabolism of environmental carcinogens, reactive oxygen species and chemotherapeutic agents by catalyzing the glutathione with electrophilic compounds. The deletion of GSTT1 and GSTM1 genes result in loss of enzyme activity. A few studies evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Soto-Quintana et al (2011) observed a tendency toward better chemotherapy response in patients with the null genotype of GSTT1 and GSTM1 polymorphisms and advanced BC. Additionally, an improved survival in patients with BC carrying the null GSTM1 genotype has been observed, and this has been explained by a better response to chemotherapeutic agents related to more effective cell killing, which in turn is related to the absence of a protective effect of the GSTM1 allele (Lizard-Nacol et al, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…Soto-Quintana et al (2011) observed a tendency toward better chemotherapy response in patients with the null genotype of GSTT1 and GSTM1 polymorphisms and advanced BC. Additionally, an improved survival in patients with BC carrying the null GSTM1 genotype has been observed, and this has been explained by a better response to chemotherapeutic agents related to more effective cell killing, which in turn is related to the absence of a protective effect of the GSTM1 allele (Lizard-Nacol et al, 1999).…”
Section: Discussionmentioning
confidence: 94%